Survey Of Hydatidosis In Cattle In Anbar Province During Period From 1/2002-12/2002: M.K.Abbass , Y.B.Ridah , M.A.Aziz - Abbass, M. K. (The Iraqi Journal of Veterinary Medicine, 2007)
Survey on distribution of hydatidosis in cattle in Anbar province have been doneduring period from 1/2002-12/2002 .This survey showing that 8.9 ℅ of cattlesuffering from hydatosis also showing that the infection of cows had beenoccurred in all months of the year ,meanwhile the bulls show resistance to theinfection of hydatidosis .There was direct relation between the age of cattle(male&female)&infection of hydatidosis .About 879 of slaughtered cattle beinginspected in Abattoir of province during the year of 2002